Day‐to‐Day Variability of Prereversal Enhancement in the Vertical Ion Drift in Response to Large‐Scale Forcing From the Lower Atmosphere - Han‐Li Liu (Space Weather)
Abstract Equatorial plasma bubbles (EPBs) are plasma density irregularities found in the equatorial ionosphere after sunset and are closely related to the upward E×B drift before it reverses to the generally downward direction at nighttime, referred to as prereversal enhancement (PRE). Although the seasonal variation of PRE and EPB have been generally associated with F and E region dynamo, large variability of EPB occurrence from one day to the next is still puzzling and poses a challenge for equatorial space weather research and forecast. This study shows that the PRE variability is strongly affected by the large‐scale lower atmosphere variability on day‐to‐day weather scales through the E region dynamo at middle latitudes in the summer hemisphere. The whole atmosphere general circulation model with interactive ionosphere electrodynamics employed in the study does not resolve EPB due to insufficient model resolution, but EPB occurrence rate can be deduced from the simulated PRE using an empirical relation. The deduced EPB rate is in good agreement with the observed rates, suggesting the important role of large‐scale dynamics and electrodynamics in preconditioning EPB and the feasibility of probabilistic forecast of EPB using a whole atmosphere model.